Marketing channels (Prentice Hall, 2001)
A text for international managers and those studying to become managers, presenting ideas that apply to any channel and any product or service on the market today. Uses plentiful examples to illustrate points, from dolls to pet food. Previous edition: c1996. DLC: Marketing channels.